THE IMPACT OF FINANCIAL STATEMENT FRAUD THROUGH THE FRAUD HEXAGON ON CONSUMER CYCLICALS SECTOR COMPANIES ON THE INDONESIA STOCK EXCHANGE IN 2020-2022 - Hakim, Mohamad Zulman; Hamdani; Galang Reza Firdaus Budiutomo; Yola Dyfa Meisari; Helen Retno Wulandari; Thorik Satria Ilmi (ZILLZELL MEDIA PRIMA, 2024)
The objective of this study is to collect empirical evidence regarding the Factors in the Fraud Hexagon Theory that can be used to detect financial statement fraud. The case study of the Consumer Cyclical Sector on the IDX in the range of 2020-2022 is used in testing the Fraud Score model. In this analysis, 89 Consumer Cyclicals companies serve as samples, purposeful sampling is used to select samples, in this study, financial statement fraud (KLK) is the dependent variable. The independent variables used are financial targets, financial stability, external pressure, CEO education, political connections, state-owned enterprises, external auditors, rationalization, and CEO duality. EViews version 13 testing software was used for data analysis of multiple linear regression analysis. This study shows that financial statement fraud is significantly influenced by external pressure and rationalization. There is no statistically significant correlation between financial objectives, financial stability, and rationalization.